Students’ Decision on The Choice of Academic Disciplines After Secondary Level Education - Bhattarai, Kriti (Kalika Journal of Multidisciplinary Studies, 2024)
This study examines the factors influencing high school students’ selection of academic disciplines in Nepal, using data collected through a structured questionnaire from 260 students in Pokhara Metropolitan City. A mixed methods approach was employed, with two colleges selected through purposive sampling and all students surveyed. Descriptive and inferential statistical analyses revealed that personal interest is the primary factor in course selection, followed by career prospects, course practicality, financial concerns, and parental guidance, while peer influence is minimal. Challenges such as financial constraints, limited career knowledge, and pressures from academic expectations and parental influence were more pronounced among students from lower-income families and those with higher GPAs. The findings highlight the need for targeted interventions, including career guidance, financial aid, and improved access to career information, to support students in making informed academic decisions.